Environment-friendly recycled concrete preparation process
By introducing high-performance additives such as hydroxyapatite-graphene composite materials, rice husk ash and recycled plastic particles into recycled concrete, the microstructure of concrete is optimized, and the problem of insufficient performance and durability in existing recycled concrete technologies is solved. Resource conservation, environmental protection and economic benefits have been improved.
Patent Information
- Application Number
- CN202411557565.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing recycled concrete technology has shortcomings in performance and durability, and the lack of in-depth research on high-performance additives and new composite materials, making it difficult to guarantee the mechanical properties.
Adopting environmentally friendly recycled concrete preparation technology, the microstructure and interface performance of concrete are optimized by introducing high-performance additives such as hydroxyapatite-graphene composite materials, rice husk ash and recycled plastic particles, and the microstructure and interface performance of concrete are formed to form a three-dimensional Internet network structure and Y-type network. Layout to improve interface adhesion and crack resistance.
It significantly improves the mechanical properties and durability of recycled concrete, reduces consumption of natural resources, reduces environmental pollution, reduces production costs, and promotes the sustainable development of the construction industry.
Smart Images

Figure CN119263740A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete preparation, and in particular to an environmentally friendly recycled concrete preparation process. Background Art
[0002] With the acceleration of urbanization, the demand for concrete in the construction industry is growing. Traditional concrete production not only consumes a large amount of natural resources, such as sand, gravel, cement, etc., but also generates a large amount of construction waste during the preparation and demolition process, which puts a serious burden on the environment. Therefore, the development of an environmentally friendly, high-performance recycled concrete that can utilize waste has become a hot topic in current research.
[0003] As a green building material, recycled concrete is mainly characterized by using construction waste as the main aggregate and is prepared through scientific proportions and advanced processes. The promotion and use of this material can not only reduce the consumption of natural resources, but also effectively alleviate the environmental pressure caused by construction waste, which is in line with the concept of sustainable development.
[0004] However, the existing recycled concrete technology still has some shortcomings in practical applications. First, since the recycled aggregate comes from construction waste, its performance and quality vary greatly, making it difficult to guarantee the mechanical properties and durability of recycled concrete. Secondly, traditional recycled concrete often ignores the optimization of microstructure and the improvement of interface performance during the preparation process, resulting in more defects and weak interfaces in the concrete, affecting its overall performance. In addition, the existing recycled concrete technology lacks in-depth research on high-performance additives and new composite materials, which limits the further improvement of the performance of recycled concrete.
[0005] Therefore, we proposed an environmentally friendly recycled concrete preparation process to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an environmentally friendly recycled concrete preparation process.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] An environmentally friendly recycled concrete comprises the following components in parts by weight: 350-564 parts of recycled concrete aggregate, 1-5 parts of hydroxyapatite-graphene composite material, 50-100 parts of rice husk ash, 50-80 parts of recycled plastic particles, 30-90 parts of fly ash, 40-70 parts of slag powder, 150-280 parts of silicate cement, 200-300 parts of medium sand, 2-6 parts of water reducer and 90-150 parts of water.
[0009] As the preferred technical solution:
[0010] The environmentally friendly recycled concrete as described above includes the following components in parts by weight: 414 parts of recycled concrete aggregate, 3 parts of hydroxyapatite-graphene composite material, 70 parts of rice husk ash, 65 parts of recycled plastic particles, 55 parts of fly ash, 60 parts of slag powder, 210 parts of silicate cement, 240 parts of medium sand, 4 parts of water reducer, and 110 parts of water.
[0011] In the environmentally friendly recycled concrete as described above, the particle size of the recycled concrete aggregate is in the range of 5-20 mm, the water absorption rate of the recycled coarse aggregate in the recycled concrete aggregate is in the range of 1%-5%; the particle size of the hydroxyapatite-graphene composite material is in the range of 10-100 nm, and the area proportion of graphene in the composite material is in the range of 0.5%-2%; the particle size of the rice husk ash is in the range of 10-45 μm, and the specific surface area of the rice husk ash is in the range of 55-100 m 2 / g, the shape of the recycled plastic particles is close to spherical to reduce its impact on the fluidity of concrete, and the particle size is controlled at 1-5mm; the fineness of the fly ash meets the 45μm sieve residue of 2%-20%, and the loss on ignition is controlled at 1%-5%; the specific surface area of the slag powder is 350-450m 2 / kg, the activity index of the slag powder meets the 7-day activity index of 75%-99%; the specific surface area of the silicate cement is 300-500m 2 / kg, the initial setting time is controlled at 50-80 minutes; the particle size of the medium sand meets the fineness modulus between 2.3-3.0, and the mud content is 1%-3%.
[0012] The environmentally friendly recycled concrete as described above, wherein the recycled concrete aggregate is reshaped by molecular structure, the molecular structure of the recycled concrete aggregate is reshaped, and the internal crystallinity and bonding strength thereof are enhanced, and the recycled concrete aggregate has an n+1-level branched structure, which increases the contact area between the aggregate and the cement paste and improves the interface bonding force; molecules capable of inducing mineralization are introduced on the surface of graphene, thereby promoting the growth of hydroxyapatite on the surface of graphene, and obtaining the hydroxyapatite-graphene composite material, wherein the hydroxyapatite and the graphene are linear in the composite material. The invention relates to a method for preparing a three-dimensional concrete microstructure by using a pre-network structure and / or constructing a secondary pre-network structure, wherein hydroxyapatite is used as a network node and graphene sheets are used as a connecting bridge to form a three-dimensional interconnected network; the rice husk ash is chemically modified and silanized to improve the hydrophobicity of its surface, and the nano-scale particles of rice husk ash are used to effectively fill the microstructure of concrete; a primary pre-network structure is designed in the recycled plastic particles, so that the recycled plastic particles form a Y-shaped network layout in the concrete, thereby enhancing the crack resistance and toughness of the concrete; the fly ash and slag powder exist in the concrete in the form of molecules or molecular clusters.
[0013] In the environmentally friendly recycled concrete as described above, in the hydroxyapatite-graphene composite material: hydroxyapatite nanosheets with an aspect ratio of 3:1 are synthesized to optimize the interface interaction between the hydroxyapatite nanosheets and the graphene; and / or an external field is used to induce the hydroxyapatite crystals to grow along the y-axis direction on the graphene surface to form an orderly crystal orientation; and / or a multi-level hydroxyapatite structure is constructed on the graphene surface, including a nanowire array and a nanosheet stack, to increase the interface area and enhance the interaction, wherein the interface area is set to IA, then:
[0014] IA=\sum_{j=1}^{m}A_j
[0015] Among them, A_j is the surface area of the j-th layer structure, and m is the number of layers;
[0016] IE=\sum_{k=1}^{l}E_k
[0017] Wherein, IE is the interaction energy, E_k is the energy of the kth interface interaction, and l is the number of interfaces; and / or the active groups on the graphene surface are used to react chemically with the phosphate or calcium ions on the hydroxyapatite surface to form stable chemical bonds, thereby improving the interface bonding strength; and / or amphiphilic polymers or biomolecules are introduced between graphene and hydroxyapatite to form a hybrid interface, which can serve as a bridge to connect graphene and hydroxyapatite and optimize the interaction between them to achieve more efficient interface energy transfer and stress dispersion.
[0018] The second aspect of the present invention provides an environmentally friendly recycled concrete preparation process, comprising the following steps:
[0019] S1: First, put silicate cement, slag powder, fly ash and medium sand into a dry mixer for dry mixing. Use the graded feeding method, that is, first add the medium sand with larger particles, then add the fine powder materials fly ash and slag powder, and finally add silicate cement to ensure that the components are evenly distributed. After the initial dry mixing, the aggregate and rice husk ash are pre-screened, and slowly added according to the particle size, and continue to dry mix until uniform;
[0020] S2: In another mixing container, use deionized water or purified water, slowly add the water reducer into the water, and stir with a stirrer to ensure that the water reducer is completely dissolved to form a uniform wet mixture;
[0021] S3: slowly add the wet mix to the dry mix, and start the wet mixer for wet mixing. During the wet mixing process, the hydroxyapatite-graphene composite material and the recycled plastic particles are pre-mixed with a small amount of water to form a slurry by a spraying method, and then the slurry is evenly sprayed into the wet mixer through a spray device to ensure that these components are evenly distributed in the concrete;
[0022] S4: Pour the evenly mixed concrete material into the mold, perform molding operation, and use a vibrating table or vibrator to compact it to ensure that the concrete is densely filled in the mold without voids to obtain recycled concrete.
[0023] As the preferred technical solution:
[0024] The above-mentioned environmentally friendly recycled concrete preparation process also includes the following pretreatment steps:
[0025] Pretreatment of recycled concrete aggregate: Select recycled concrete aggregate with a particle size of 5-20mm, ensure that its water absorption rate is 1%-5%, and calculate its apparent density according to the water absorption rate W of the aggregate by the formula ρ=2.7 / (2.7W+1), where W is the water absorption rate and ρ is the apparent density of the recycled concrete aggregate, so as to facilitate subsequent batching, clean the aggregate and remove impurities and dust on the surface;
[0026] Preparation of hydroxyapatite-graphene composite material: hydroxyapatite is prepared by chemical precipitation method, and graphene is uniformly deposited on its surface to form a composite material, and the area ratio of graphene in the composite material is controlled to be 0.5%-2%, and the particle size is 10-100nm;
[0027] Preparation and treatment of rice husk ash: Incinerate rice husk at high temperature, control the temperature at 600-800°C to obtain rice husk ash, and ensure that the particle size of the rice husk ash is 10-45μm and the specific surface area is 55-100m2 / g.
[0028] The above-mentioned environmentally friendly recycled concrete preparation process also includes the following pretreatment steps:
[0029] Treatment of recycled plastic particles: Select recycled plastic particles with a shape close to spherical, and control the particle size to 1-5mm to reduce its impact on the fluidity of concrete, and clean and dry the particles;
[0030] Preparation of other components: ensure that the fineness of fly ash meets the requirements of 45μm sieve residue between 2% and 20%, loss on ignition is controlled at 1% to 5%, specific surface area of slag powder is controlled at 350-450m2 / kg, 7-day activity index is 75% to 99%, specific surface area of Portland cement is 300-500m2 / kg, initial setting time is controlled at 50-80 minutes, particle size of medium sand meets the requirements of fineness modulus between 2.3 and 3.0, and mud content is 1% to 3%.
[0031] The above-mentioned environmentally friendly recycled concrete preparation process further includes:
[0032] S5: The formed concrete is cured, the curing temperature is controlled within the range of 20±5℃, the humidity is maintained above 90%, and the curing time is 28-80 days.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] Resource conservation and environmental protection synergy: By using recycled concrete aggregates, this technology significantly reduces the demand for mining new sand and gravel and other natural resources. Recycled aggregates can partially or completely replace natural aggregates, thereby effectively protecting natural resources. The recycling of construction waste (such as the use of recycled plastic particles) not only reduces the stacking and landfilling of waste, but also reduces pollution to the environment.
[0035] Performance improvement and material innovation: Through fine proportioning and the introduction of high-performance additives, the mechanical properties and durability of recycled concrete have been significantly improved. These additives form a reinforced microstructure in the concrete and improve the overall performance of the material. The reuse of industrial waste such as rice husk ash and fly ash not only improves the performance of concrete, but also brings new innovations to the building materials industry. Rice husk ash can improve the microstructure of concrete, increase its density and strength; recycled plastic particles can be used as an admixture for recycled concrete, replacing part of the aggregate and reducing costs. When the two work together, the concrete has an excellent microstructure while also reducing its cost.
[0036] Economic and social benefits: Due to the large amount of low-cost recycled materials used, this technology helps to reduce the production cost of concrete and improve the economic benefits of enterprises. At the same time, it also provides more competitive product options for the construction industry. The promotion and application of this technology helps to promote the sustainable development of society. By reducing resource consumption and environmental pollution, it brings long-term ecological and environmental benefits to society. In addition, it also promotes the green transformation of the construction industry and lays a solid foundation for future sustainable development.
[0037] In summary, this environmentally friendly recycled concrete technology has demonstrated significant effects and benefits in resource conservation, environmental protection, performance improvement, material innovation, economic benefits and social benefits through synergy. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The damage form of the recycled concrete after the implementation test of the present invention is Figure 1 ;
[0039] Figure 2 The damage form of the recycled concrete after the implementation test of the present invention is Figure 2 ;
[0040] Figure 3The damage form of the recycled concrete after the implementation test of the present invention is Figure 3 ;
[0041] Figure 4 The damage form of the recycled concrete after the implementation test of the present invention is Figure 4 . DETAILED DESCRIPTION
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."
[0043] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0044] An environmentally friendly recycled concrete comprises the following components in parts by weight: 350-564 parts of recycled concrete aggregate, 1-5 parts of hydroxyapatite-graphene composite material, 50-100 parts of rice husk ash, 50-80 parts of recycled plastic particles, 30-90 parts of fly ash, 40-70 parts of slag powder, 150-280 parts of silicate cement, 200-300 parts of medium sand, 2-6 parts of water reducer and 90-150 parts of water.
[0045] Specifically, the particle size of the recycled concrete aggregate is in the range of 5-20 mm, and the water absorption rate of the recycled coarse aggregate in the recycled concrete aggregate is in the range of 1%-5%; the particle size of the hydroxyapatite-graphene composite material is in the range of 10-100 nm, and the area proportion of graphene in the composite material is in the range of 0.5%-2%; the particle size of the rice husk ash is in the range of 10-45 μm, and the specific surface area of the rice husk ash is in the range of 55-100 m 2 / g, the shape of the recycled plastic particles is close to spherical to reduce its impact on the fluidity of concrete, and the particle size is controlled at 1-5mm; the fineness of the fly ash meets the 45μm sieve residue of 2%-20%, and the loss on ignition is controlled at 1%-5%; the specific surface area of the slag powder is 350-450m 2 / kg, the activity index of the slag powder meets the 7-day activity index of 75%-99%; the specific surface area of the silicate cement is 300-500m 2 / kg, the initial setting time is controlled at 50-80 minutes; the particle size of the medium sand meets the fineness modulus between 2.3-3.0, and the mud content is 1%-3%.
[0046] The recycled concrete aggregate is reshaped by molecular structure, and its internal crystallinity and bonding strength are enhanced. The recycled concrete aggregate has an n+1-level branched structure, which increases the contact area between the aggregate and the cement paste and improves the interfacial bonding force. Molecules (polydopamine) that can induce mineralization are introduced on the surface of graphene to promote the growth of hydroxyapatite on the surface of graphene, thereby obtaining the hydroxyapatite-graphene composite material, wherein hydroxyapatite and graphene are linearly arranged in the composite material. And / or construct a secondary pre-network structure, in which hydroxyapatite serves as a network node and graphene sheets serve as a connecting bridge to form a three-dimensional interconnected network; the rice husk ash is chemically modified and silanized to improve the hydrophobicity of its surface, and the nano-scale particles of rice husk ash are used to achieve its effective filling in the concrete microstructure; a primary pre-network structure is designed in the recycled plastic particles so that the recycled plastic particles form a Y-shaped network layout in the concrete, thereby enhancing the crack resistance and toughness of the concrete; the fly ash and slag powder exist in the concrete in the form of molecules or molecular clusters.
[0047] The following is a specific example, which details how to implement the various technical points described in environmentally friendly recycled concrete:
[0048] Example: Preparation of environmentally friendly recycled concrete
[0049] 1. Reshaping the molecular structure of recycled concrete aggregate
[0050] Goal: To enhance the crystallinity and bonding strength within the aggregate and create an n+1 level branching structure.
[0051] Operation: Crushed and screened waste concrete blocks are selected as raw aggregates. The molecular structure of the aggregates is reshaped by combining high temperature treatment (e.g., calcination at 800°C for 2 hours) and chemical activators (such as soaking in sodium silicate solution).
[0052] Data: The crystallinity of the treated aggregate increased by 30%, and the bonding strength increased by 25%. The n+1 branching structure increased the contact area between the aggregate and the cement paste by 40%, thus significantly improving the interfacial bonding force.
[0053] 2. Preparation of hydroxyapatite-graphene composites
[0054] Objective: To introduce polydopamine on the graphene surface to promote the growth of hydroxyapatite and form a linear arrangement or secondary pre-network structure.
[0055] Operation: First, the graphene sheet is immersed in a polydopamine solution for 24 hours to attach polydopamine molecules to its surface. Then, a mineralization reaction is carried out in a solution containing calcium ions and phosphate ions to promote the growth of hydroxyapatite on the graphene surface.
[0056] Data: The ratio of hydroxyapatite to graphene in the composite material reaches 1:0.05. Hydroxyapatite acts as a network node and graphene sheets act as a connecting bridge, forming a stable three-dimensional interconnected network structure.
[0057] 3. Chemical modification and silanization of rice husk ash
[0058] Objective: To improve the hydrophobicity of rice husk ash surface and achieve its effective filling in concrete.
[0059] Operation: Rice husk ash is soaked in a silanizing agent (such as methyltrimethoxysilane), then dried and ground.
[0060] Data: The hydrophobicity of rice husk ash increased by 70% after treatment, and its nano-scale particles can be evenly dispersed in concrete, effectively filling microscopic pores.
[0061] 4. Pre-network structure design of recycled plastic particles
[0062] Goal: To create a Y-shaped network structure of recycled plastic particles in concrete to enhance crack resistance and toughness.
[0063] Operation: Select the appropriate type and size of recycled plastic particles, and form them into a structure with a Y-type network layout through heat treatment and pressure molding technology.
[0064] Data: The distribution of recycled plastic particles in concrete forms a distinct Y-shaped network layout, which increases the concrete's crack resistance by 20% and its toughness by 15%.
[0065] 5. Utilization of fly ash and slag powder
[0066] Objective: To make fly ash and slag powder exist in concrete in the state of molecules or molecular clusters.
[0067] Operation: Mix fly ash and slag powder with cement, water, etc. and ensure that they are evenly dispersed in the concrete by stirring thoroughly.
[0068] Data: The addition amount of fly ash and slag powder accounts for 15% and 10% of the total weight of concrete respectively. They exist in the concrete in the form of tiny molecules or molecular clusters, effectively improving the strength and durability of concrete.
[0069] Specifically, in the hydroxyapatite-graphene composite material: synthesize hydroxyapatite nanosheets with an aspect ratio of 3:1 to optimize the interface interaction between the nanosheets and the graphene; and / or use an external field to induce the growth of hydroxyapatite crystals on the graphene surface along the y-axis direction to form an ordered crystal orientation; and / or construct a multi-layer hydroxyapatite structure on the graphene surface, including a nanowire array and a nanosheet stack, to increase the interface area and enhance the interaction, wherein the interface area is set to IA, then: IA = \sum_{j=1}^{m}A_j; wherein A_j is the surface area of the j-th layer structure, and m is the number of layers; IE=\sum_{k=1}^{l}E_k; wherein IE is the interaction energy, E_k is the energy of the kth interface interaction, and l is the number of interfaces; and / or utilizing the active groups on the graphene surface to react chemically with the phosphate or calcium ions on the hydroxyapatite surface to form stable chemical bonds, thereby enhancing the interfacial bonding strength; and / or introducing amphiphilic polymers or biomolecules between graphene and hydroxyapatite to form a hybrid interface, which can serve as a bridge to connect graphene and hydroxyapatite and optimize the interaction between them to achieve more efficient interfacial energy transfer and stress dispersion.
[0070] The following is a specific example to illustrate how to achieve specific performance optimization of "hydroxyapatite-graphene composite material" in environmentally friendly recycled concrete:
[0071] Example: Optimizing the preparation and properties of hydroxyapatite-graphene composites
[0072] 1. Synthesis of hydroxyapatite nanosheets with an aspect ratio of 3:1
[0073] Objective: To synthesize hydroxyapatite nanosheets with an aspect ratio of 3:1 to optimize the interfacial interaction with graphene.
[0074] Operation: Hydroxyapatite nanosheets are synthesized by chemical precipitation under strictly controlled reaction conditions (such as temperature, pH value, and reactant concentration). The shape and size of the nanosheets can be controlled by adjusting the reaction time and the addition rate of the precipitant.
[0075] Data: The synthesized hydroxyapatite nanosheets have an average aspect ratio of 3:1, are uniform in size, and have significantly optimized interfacial interactions with graphene.
[0076] 2. Use external field to induce crystal orientation growth
[0077] Objective: To use an external electric or magnetic field to induce the orderly growth of hydroxyapatite crystals along the y-axis on the graphene surface.
[0078] Operation: During the hydroxyapatite synthesis process, an external electric field or magnetic field is introduced. By adjusting the field strength and direction, the growth direction of the hydroxyapatite crystal is controlled.
[0079] Data: Under the action of an external field, hydroxyapatite crystals form an ordered y-axis orientation on the graphene surface, improving the structure and mechanical properties of the composite material.
[0080] 3. Construction of multi-layered hydroxyapatite structure
[0081] Objective: To construct multi-level hydroxyapatite structures including nanowire arrays and nanosheet stacks on the graphene surface.
[0082] Operation: First, a layer of hydroxyapatite nanowire array is deposited on the graphene surface. Then, hydroxyapatite nanosheets are deposited on this basis to form a multilayer stacking structure.
[0083] Data: Through calculation, the interface area (IA) increases significantly, and the interaction energy (IE) also increases. The multi-level structure provides more interfaces and stronger interactions.
[0084] 4. Use chemical reactions to improve interfacial bonding
[0085] Objective: To form stable chemical bonds through chemical reactions between the active groups on the graphene surface and the phosphate or calcium ions on the hydroxyapatite surface.
[0086] Operation: During the synthesis process, add an appropriate amount of cross-linking agent or catalyst to promote the chemical reaction between graphene and hydroxyapatite.
[0087] Data: Chemical analysis confirmed that a stable chemical bond was formed between graphene and hydroxyapatite, and the interface bonding strength was significantly improved.
[0088] 5. Introducing amphiphilic polymers to form hybrid interfaces
[0089] Objective: To introduce an amphiphilic polymer between graphene and hydroxyapatite to form a hybrid interface.
[0090] Operation: Select a polymer with amphiphilic properties, such as polyethylene glycol (PEG), and add it to the mixture of graphene and hydroxyapatite. Through sufficient stirring and heat treatment, the polymer forms a stable hybrid interface between the two.
[0091] Data: After the introduction of amphiphilic polymers, the formation of hybrid interfaces significantly optimized the interaction between graphene and hydroxyapatite, achieving more efficient interfacial energy transfer and stress dispersion. At the same time, the mechanical properties and durability of the composite materials were also improved.
[0092] Embodiment 1
[0093] An environmentally friendly recycled concrete comprises the following components in parts by weight: 350 parts of recycled concrete aggregate (Xuchang Jian'an District Weilun Recycling Resources Co., Ltd.), 1 part of hydroxyapatite-graphene composite material, 50 parts of rice husk ash (Lingshou County Jiayuan Mineral Products Processing Plant), 50 parts of recycled plastic particles (ABS black recycled material plastic particles, Hebei Cangzhou Haoyuan Spiral Pipe Factory), 30 parts of fly ash (China Building Materials Group), 40 parts of slag powder (China Building Materials Group), 150 parts of silicate cement (China Building Materials Group), 200 parts of medium sand (China Building Materials Group), 2 parts of water reducer, and 90 parts of water.
[0094] The embodiment also provides an environmentally friendly recycled concrete preparation process, comprising the following steps: S1: first, silicate cement, slag powder, fly ash and medium sand are put into a dry mixer for dry mixing. The dry mixing process should be carried out at an ambient temperature of 20°C and a relative humidity of 40%. A graded feeding method is adopted, that is, medium sand with larger particles is first added, then fine powder materials fly ash and slag powder are added, and finally silicate cement is added to ensure that each component is evenly distributed. The speed of the dry mixer should be controlled between 15rpm and the mixing time is 5 minutes. After the initial dry mixing is uniform, the aggregate and rice husk ash are pre-screened, and slowly added according to the particle size, and the dry mixing is continued until uniform;
[0095] S2: In another mixing container, use deionized water or purified water. The deionized water or purified water used should meet the standards of conductivity 2μS / cm and pH value 6.5. Slowly add the water reducer into the water. The concentration of the water reducer is controlled at 5%. The adding speed is controlled at 0.5ml per second. Stir with a stirrer to ensure that the water reducer is completely dissolved to form a uniform wet mixture.
[0096] S3: Slowly add the wet mix to the dry mix, and start the wet mixer for wet mixing. The speed of the wet mixer is controlled at 30 rpm, and the mixing time is 10 minutes. During the wet mixing process, the hydroxyapatite-graphene composite material and the recycled plastic particles are pre-mixed with a small amount of water to form a slurry by a spraying method, and then evenly sprayed into the wet mixer through a spray device. The spray particle size should be controlled at 60 μm, and the spray speed should be controlled at 0.5 ml per second to ensure that these components are evenly distributed in the concrete.
[0097] S4: pour the mixed concrete material into the mold, perform molding operation, and use a vibration table for compaction. The vibration frequency of the vibration table is controlled at 50 Hz, the amplitude is controlled at 0.5 mm, and the vibration time is 1 minute to ensure that the concrete is densely filled in the mold without voids to obtain recycled concrete;
[0098] S5: The formed concrete is cured with the curing temperature controlled at 15°C and the humidity maintained at 90% for 28 days.
[0099] The following preprocessing steps are also included:
[0100] Pretreatment of recycled concrete aggregate: Select recycled concrete aggregate with a particle size within the range of 5mm, ensure that its water absorption rate is 1%, and calculate its apparent density according to the water absorption rate W of the aggregate by the formula ρ=2.7 / (2.7W+1), where W is the water absorption rate and ρ is the apparent density of the recycled concrete aggregate, so as to facilitate subsequent batching, clean the aggregate and remove impurities and dust on the surface;
[0101] Preparation of hydroxyapatite-graphene composite material: hydroxyapatite is prepared by chemical precipitation method, and graphene is uniformly deposited on its surface to form a composite material, and the area ratio of graphene in the composite material is controlled to be 0.5%, and the particle size is 10nm;
[0102] Preparation and treatment of rice husk ash: Incinerate rice husk at high temperature, control the temperature at 600℃, and obtain rice husk ash, ensuring that the particle size of rice husk ash is 10μm and the specific surface area is 55m 2 / g;
[0103] Treatment of recycled plastic particles: Select recycled plastic particles with a shape close to spherical and a particle size of 1 mm to reduce its impact on the fluidity of concrete, and clean and dry the particles;
[0104] Preparation of other components: Ensure that the fineness of fly ash meets 45μm sieve residue 10%, ignition loss 1%, and the specific surface area of slag powder is controlled at 350m 2 / kg, 7-day activity index is 75%, the specific surface area of silicate cement is 150m 2 / kg, initial setting time 50 minutes, medium sand particle size meets the fineness modulus of 2.3, and mud content 1%.
[0105] Embodiment 2
[0106] An environmentally friendly recycled concrete comprises the following components in parts by weight: 381 parts of recycled concrete aggregate, 2 parts of hydroxyapatite-graphene composite material, 60 parts of rice husk ash, 65 parts of recycled plastic particles, 45 parts of fly ash, 50 parts of slag powder, 180 parts of silicate cement, 220 parts of medium sand, 3 parts of water reducer and 110 parts of water.
[0107] The embodiment also provides an environmentally friendly recycled concrete preparation process, comprising the following steps: S1: first, silicate cement, slag powder, fly ash and medium sand are put into a dry mixer for dry mixing. The dry mixing process should be carried out at an ambient temperature of 22° C. and a relative humidity of 45%. A graded feeding method is adopted, that is, medium sand with larger particles is first added, then fine powder materials fly ash and slag powder are added, and finally silicate cement is added to ensure that each component is evenly distributed. The speed of the dry mixer should be controlled at 18 rpm, and the mixing time is 8 minutes. After the initial dry mixing is uniform, the aggregate and rice husk ash are pre-screened, and slowly added according to the particle size, and the dry mixing is continued until uniform;
[0108] S2: In another mixing container, use deionized water or purified water. The deionized water or purified water used should meet the standards of conductivity less than 10μS / cm and pH value of 7.0. Slowly add the water reducer into the water. The concentration of the water reducer is controlled at 7%. The adding speed is controlled at 0.7ml per second. Stir with a stirrer to ensure that the water reducer is completely dissolved to form a uniform wet mixture.
[0109] S3: Slowly add the wet mix to the dry mix, and start the wet mixer for wet mixing. The speed of the wet mixer is controlled at 40 rpm, and the mixing time is 15 minutes. During the wet mixing process, the hydroxyapatite-graphene composite material and the recycled plastic particles are pre-mixed with a small amount of water to form a slurry by a spraying method, and then evenly sprayed into the wet mixer through a spray device. The spray particle size should be controlled at 60 μm, and the spray speed should be controlled at 0.7 ml per second to ensure that these components are evenly distributed in the concrete.
[0110] S4: pour the mixed concrete material into the mold, perform molding operation, and use a vibration table for compaction. The vibration frequency of the vibration table is controlled at 60 Hz, the amplitude is controlled at 0.6 mm, and the vibration time is 2 minutes to ensure that the concrete is densely filled in the mold without voids to obtain recycled concrete;
[0111] S5: The formed concrete is cured, the curing temperature is controlled at 20°C, the humidity is kept above 90%, and the curing time is 35 days.
[0112] The following preprocessing steps are also included:
[0113] Pretreatment of recycled concrete aggregate: Select recycled concrete aggregate with a particle size within the range of 8mm, ensure that its water absorption rate is 2%, and calculate its apparent density according to the water absorption rate W of the aggregate by the formula ρ=2.7 / (2.7W+1), where W is the water absorption rate and ρ is the apparent density of the recycled concrete aggregate, so as to facilitate subsequent batching, clean the aggregate and remove impurities and dust on the surface;
[0114] Preparation of hydroxyapatite-graphene composite material: hydroxyapatite is prepared by chemical precipitation method, and graphene is uniformly deposited on its surface to form a composite material, and the area ratio of graphene in the composite material is controlled to be 0.8%, and the particle size is 30nm;
[0115] Preparation and treatment of rice husk ash: The rice husk is incinerated at high temperature, and the temperature is controlled at 650℃ to obtain rice husk ash, ensuring that the particle size of the rice husk ash is 25μm and the specific surface area is 60m 2 / g;
[0116] Treatment of recycled plastic particles: Select recycled plastic particles with a shape close to spherical and a particle size of 2 mm to reduce its impact on the fluidity of concrete, and clean and dry the particles;
[0117] Preparation of other components: Ensure that the fineness of fly ash meets the 45μm sieve residue at 50%, the loss on ignition is controlled at 2%, and the specific surface area of slag powder is controlled at 380m 2 / kg, 7-day activity index is 80%, and the specific surface area of silicate cement is 350m 2 / kg, the initial setting time is controlled at 55 minutes, the particle size of medium sand meets the fineness modulus of 2.5 and the mud content is 2%.
[0118] Embodiment 3
[0119] An environmentally friendly recycled concrete comprises the following components in parts by weight: 464 parts of recycled concrete aggregate, 3 parts of hydroxyapatite-graphene composite material, 70 parts of rice husk ash, 65 parts of recycled plastic particles, 70 parts of fly ash, 60 parts of slag powder, 210 parts of silicate cement, 280 parts of medium sand, 4 parts of water reducer and 120 parts of water.
[0120] The embodiment also provides an environmentally friendly recycled concrete preparation process, comprising the following steps: S1: first, silicate cement, slag powder, fly ash and medium sand are put into a dry mixer for dry mixing. The dry mixing process should be carried out at an ambient temperature of 28°C and a relative humidity of 55%. A graded feeding method is adopted, that is, medium sand with larger particles is first added, then fine powder materials fly ash and slag powder are added, and finally silicate cement is added to ensure that each component is evenly distributed. The speed of the dry mixer should be controlled between 25rpm and the mixing time is 12 minutes. After the initial dry mixing is uniform, the aggregate and rice husk ash are pre-screened, and slowly added according to the particle size, and the dry mixing is continued until uniform;
[0121] S2: In another mixing container, use deionized water or purified water. The deionized water or purified water used should meet the standards of conductivity less than 10μS / cm and pH value of 7.0. Slowly add the water reducer into the water. The concentration of the water reducer is controlled between 7%. The adding speed is controlled at 0.8ml per second. Stir with a stirrer to ensure that the water reducer is completely dissolved to form a uniform wet mixture.
[0122] S3: Slowly add the wet mix to the dry mix, and start the wet mixer for wet mixing. The speed of the wet mixer is controlled between 50rpm and the mixing time is 20 minutes. During the wet mixing process, the hydroxyapatite-graphene composite material and the recycled plastic particles are pre-mixed with a small amount of water to form a slurry by a spraying method, and then evenly sprayed into the wet mixer through a spray device. The spray particle size should be controlled between 70μm and the spray speed should be controlled at 0.7ml per second to ensure that these components are evenly distributed in the concrete.
[0123] S4: pour the mixed concrete material into the mold, perform molding operation, and use a vibration table for compaction. The vibration frequency of the vibration table is controlled at 80 Hz, the amplitude is controlled at 0.8 mm, and the vibration time is 3 minutes to ensure that the concrete is densely filled in the mold without voids to obtain recycled concrete;
[0124] S5: The formed concrete is cured, the curing temperature is controlled within 22°C, the humidity is maintained above 90%, and the curing time is 50 days.
[0125] The following preprocessing steps are also included:
[0126] Pretreatment of recycled concrete aggregate: Select recycled concrete aggregate with a particle size within the range of 15mm, ensure that its water absorption rate is 3%, and calculate its apparent density according to the water absorption rate W of the aggregate by the formula ρ=2.7 / (2.7W+1), where W is the water absorption rate and ρ is the apparent density of the recycled concrete aggregate, so as to facilitate subsequent batching, clean the aggregate and remove impurities and dust on the surface;
[0127] Preparation of hydroxyapatite-graphene composite material: hydroxyapatite is prepared by chemical precipitation method, and graphene is uniformly deposited on its surface to form a composite material, and the area ratio of graphene in the composite material is controlled to be 0.8%, and the particle size is 60nm;
[0128] Preparation and treatment of rice husk ash: Incinerate rice husk at high temperature, control the temperature at 700℃, and obtain rice husk ash, ensuring that the particle size of rice husk ash is 25μm and the specific surface area is 75m 2 / g;
[0129] Treatment of recycled plastic particles: Select recycled plastic particles with a shape close to spherical and a particle size of 4 mm to reduce its impact on the fluidity of concrete, and clean and dry the particles;
[0130] Preparation of other components: Ensure that the fineness of fly ash meets the 45μm sieve residue at 15%, the loss on ignition is controlled at 3%, and the specific surface area of slag powder is controlled at 410m 2 / kg, 7-day activity index is 80%, and the specific surface area of silicate cement is 400m 2 / kg, the initial setting time is controlled at 65 minutes, the particle size of medium sand meets the fineness modulus of 2.7, and the mud content is 2%.
[0131] Embodiment 4
[0132] An environmentally friendly recycled concrete comprises the following components in parts by weight: 564 parts of recycled concrete aggregate, 5 parts of hydroxyapatite-graphene composite material, 100 parts of rice husk ash, 80 parts of recycled plastic particles, 90 parts of fly ash, 70 parts of slag powder, 280 parts of silicate cement, 300 parts of medium sand, 6 parts of water reducer and 150 parts of water.
[0133] The embodiment also provides an environmentally friendly recycled concrete preparation process, comprising the following steps: S1: first, silicate cement, slag powder, fly ash and medium sand are put into a dry mixer for dry mixing. The dry mixing process should be carried out at an ambient temperature of 30°C and a relative humidity of 60%. A graded feeding method is adopted, that is, medium sand with larger particles is first added, then fine powder materials fly ash and slag powder are added, and finally silicate cement is added to ensure that each component is evenly distributed. The speed of the dry mixer should be controlled at 30 rpm, and the mixing time is 20 minutes. After the initial dry mixing is uniform, the aggregate and rice husk ash are pre-screened, and slowly added according to the particle size, and the dry mixing is continued until uniform;
[0134] S2: In another mixing container, use deionized water or purified water. The deionized water or purified water used should meet the standards of conductivity less than 10μS / cm and pH value of 7.5. Slowly add the water reducer into the water. The concentration of the water reducer is controlled at 10%. The adding speed is controlled at 1.0 ml per second. Stir with a stirrer to ensure that the water reducer is completely dissolved to form a uniform wet mixture.
[0135] S3: Slowly add the wet mix to the dry mix, and start the wet mixer for wet mixing. The speed of the wet mixer is controlled at 60 rpm, and the mixing time is 30 minutes. During the wet mixing process, the hydroxyapatite-graphene composite material and the recycled plastic particles are pre-mixed with a small amount of water to form a slurry by a spraying method, and then evenly sprayed into the wet mixer through a spray device. The spray particle size should be controlled at 100 μm, and the spray speed should be controlled at 1.0 ml per second to ensure that these components are evenly distributed in the concrete.
[0136] S4: pour the mixed concrete material into the mold, perform molding operation, and use a vibration table for compaction. The vibration frequency of the vibration table is controlled at 100 Hz, the amplitude is controlled at 1.0 mm, and the vibration time is 10 minutes to ensure that the concrete is densely filled in the mold without voids to obtain recycled concrete;
[0137] S5: The formed concrete is cured, the curing temperature is controlled at 25°C, the humidity is maintained above 90%, and the curing time is 80 days.
[0138] The following preprocessing steps are also included:
[0139] Pretreatment of recycled concrete aggregate: Select recycled concrete aggregate with a particle size within 20 mm, ensure that its water absorption rate is 5%, and calculate its apparent density according to the water absorption rate W of the aggregate by the formula ρ=2.7 / (2.7W+1), where W is the water absorption rate and ρ is the apparent density of the recycled concrete aggregate, so as to facilitate subsequent batching, clean the aggregate and remove impurities and dust on the surface;
[0140] Preparation of hydroxyapatite-graphene composite material: hydroxyapatite is prepared by chemical precipitation method, and graphene is uniformly deposited on its surface to form a composite material, and the area proportion of graphene in the composite material is controlled to be 2%, and the particle size is 100nm;
[0141] Preparation and treatment of rice husk ash: Incinerate rice husk at high temperature, control the temperature at 800℃, and obtain rice husk ash, ensuring that the particle size of rice husk ash is 45μm and the specific surface area is 100m 2 / g;
[0142] Treatment of recycled plastic particles: Select recycled plastic particles with a shape close to spherical and a particle size of 5 mm to reduce its impact on the fluidity of concrete, and clean and dry the particles;
[0143] Preparation of other components: Ensure that the fineness of fly ash meets the 45μm sieve residue at 20%, the loss on ignition is controlled at 5%, and the specific surface area of slag powder is controlled at 450m 2 / kg, 7-day activity index is 99%, and the specific surface area of silicate cement is 500m 2 / kg, the initial setting time is controlled at 80 minutes, the particle size of medium sand meets the fineness modulus of 3.0 and the mud content is 3%.
[0144] Comparative Example 1
[0145] An environmentally friendly recycled concrete preparation process is basically the same as Example 4, except that the hydroxyapatite-graphene composite material is removed, and other components and steps remain unchanged.
[0146] Comparative Example 2
[0147] An environmentally friendly recycled concrete preparation process is basically the same as the fourth embodiment, the only difference being that rice husk ash is removed and recycled plastic particles are used.
[0148] Comparative Example 3
[0149] An environmentally friendly recycled concrete preparation process is basically the same as the fourth embodiment, except that the hydroxyapatite-graphene composite material is removed and hydroxyapatite and graphene materials are added separately instead.
[0150] Comparative Example 4
[0151] An environmentally friendly recycled concrete preparation process is basically the same as the fourth embodiment, except that the screening step of medium sand is omitted and unscreened medium sand is directly used, and other components and steps remain unchanged.
[0152] The concrete prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 was tested:
[0153] Compressive strength test:
[0154] National standard: GB / T 50081 "Standard for test methods of mechanical properties of ordinary concrete"
[0155] Test method: Prepare concrete test blocks of standard size (usually 150mm×150mm×150mm), and after curing to the specified age, conduct a compressive strength test on a pressure testing machine, record the maximum load when the test block fails, and calculate the compressive strength.
[0156] Flexural strength test:
[0157] National standard: GB / T 50081 "Standard for test methods of mechanical properties of ordinary concrete"
[0158] Test method: Prepare concrete beam specimens of standard size, and after curing to the specified age, conduct flexural strength test on a three-point bending device, record the maximum load when the specimen is destroyed, and calculate the flexural strength.
[0159] Durability testing (such as impermeability, frost resistance, etc.):
[0160] National standard: GB / T 50082 "Standard for test methods of long-term performance and durability of ordinary concrete"
[0161] Testing method: According to specific durability indicators, such as impermeability, the ability of concrete to resist pressure water penetration can be measured through water seepage test; frost resistance can be evaluated through freeze-thaw cycle test to evaluate the durability of concrete in freeze-thaw environment.
[0162] Component analysis (such as aggregate, cement, etc.):
[0163] National standard: GB / T 176 "Cement Chemical Analysis Methods" etc.
[0164] Detection method: The concrete samples are crushed, ground, and then chemically analyzed to determine the content of each component, such as calcium oxide, silicon oxide, and other components in cement clinker.
[0165] The results are shown in Table 1:
[0166] Table 1
[0167]
[0168] Through the above Table 1, it can be directly obtained that the environmentally friendly recycled concrete of Examples 1 to 4 has better performance in terms of compressive strength, flexural strength, impermeability and frost resistance. In terms of compressive strength, from Example 1 to Example 4, the compressive strength of concrete gradually increases. This shows that with the optimization of the preparation process or the fine-tuning of the components, the compressive capacity of concrete has been enhanced. In particular, Example 4 reached 48.2MPa, which is the highest compressive strength among the four embodiments. In terms of flexural strength, it also shows an increasing trend similar to the compressive strength. The flexural strength of Example 4 is the highest, reaching 8.8MPa, which shows that it has better resistance when subjected to bending force. In terms of impermeability, Example 1 is slightly lower, at P11, while Examples 2, 3, and 4 all reach P12. This shows that the preparation conditions of the embodiment drop sharply after being lower than a value. In terms of frost resistance, the grade of Example 1 is F180, while Examples 2 and 3 are both increased to F195, and Example 4 even reaches F200. This shows that the concrete of Example 4 has the best durability in a freeze-thaw environment.
[0169] From Example 1 to Example 4, the key performance indicators of the environmentally friendly recycled concrete, such as compressive strength, flexural strength, impermeability and frost resistance, all show a trend of gradual improvement, especially Example 4, which shows excellent performance in all aspects, which provides strong support for its application in practical engineering. Because the preparation conditions exceed the lower limit, the performance indicators of Example 1 are lower than those of other examples.
[0170] Reference Figure 1-4 In Example 4 and Comparative Example 1, where other conditions are the same, Example 4 is significantly better than Comparative Example 1 in all indicators. The main difference is that the hydroxyapatite-graphene composite material is removed in Comparative Example 1. This shows that the addition of hydroxyapatite-graphene composite material plays an important role in improving the comprehensive performance of concrete.
[0171] Example 4 is compared with Comparative Example 2, in which rice husk ash and recycled plastic particles are removed, which shows that the addition of these two components has a positive effect on the performance of concrete, especially in improving the anti-permeability and anti-freeze properties.
[0172] Compared with Example 3, the performance of Example 4 is further improved on the basis of Example 3. In Example 3, hydroxyapatite and graphene materials are added separately instead of using composite materials. This shows that the composite form of hydroxyapatite and graphene plays a better synergistic role in concrete, thereby improving the overall performance.
[0173] The performance of Example 4 is significantly better than that of Comparative Example 4. The main difference is that the screening step of medium sand is omitted in Comparative Example 4. This shows that the screening process of medium sand has an important influence on the performance of concrete, which may be because the medium sand after screening has a more uniform particle size distribution, thereby improving the overall uniformity and performance of concrete.
[0174] In summary, by comparing the data of Example 4 with Comparative Examples 1 to 4, we can draw the following conclusions: The addition of hydroxyapatite-graphene composite material significantly improves the performance of concrete. The use of rice husk ash and recycled plastic particles also has a positive effect on the performance of concrete, especially in terms of impermeability and frost resistance. The composite form of hydroxyapatite and graphene can play a more synergistic role than the use of these two materials alone to improve the performance of concrete. The screening treatment of medium sand has an important influence on the performance of concrete because it affects the uniformity and structural density of concrete.
[0175] Rice husk ash can improve the microstructure of concrete, increase its density and strength; recycled plastic particles can be used as admixtures for recycled concrete, replacing part of the aggregate and reducing costs. The combined effect of the two can make concrete have an excellent microstructure while reducing its cost.
[0176] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An environmentally friendly recycled concrete, characterized in that: The invention comprises the following components in parts by weight: 350-564 parts of recycled concrete aggregate, 1-5 parts of hydroxyapatite-graphene composite material, 50-100 parts of rice husk ash, 50-80 parts of recycled plastic particles, 30-90 parts of fly ash, 40-70 parts of slag powder, 150-280 parts of silicate cement, 200-300 parts of medium sand, 2-6 parts of water reducer and 90-150 parts of water.
2. The environmentally friendly recycled concrete according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 414 parts of recycled concrete aggregate, 3 parts of hydroxyapatite-graphene composite material, 70 parts of rice husk ash, 65 parts of recycled plastic particles, 55 parts of fly ash, 60 parts of slag powder, 210 parts of silicate cement, 240 parts of medium sand, 4 parts of water reducer and 110 parts of water.
3. The environmentally friendly recycled concrete according to claim 1, characterized in that: The particle size of the recycled concrete aggregate is in the range of 5-20 mm, and the water absorption rate of the recycled coarse aggregate in the recycled concrete aggregate is in the range of 1%-5%; The particle size of the hydroxyapatite-graphene composite material is 10-100 nm, and the area proportion of graphene in the composite material is 0.5%-2%; The particle size of the rice husk ash particles is 10-45 μm, and the specific surface area of the rice husk ash is 55-100 m 2 / g, the shape of the recycled plastic particles is close to spherical to reduce their impact on the fluidity of concrete, and the particle size is controlled at 1-5mm; The fineness of the fly ash satisfies the requirement that the residue on a 45 μm sieve is between 2% and 20%, and the loss on ignition is controlled between 1% and 5%. The specific surface area of the slag powder is 350-450m 2 / kg, the activity index of slag powder meets the 7-day activity index of 75%-99%; The specific surface area of the silicate cement is 300-500m 2 / kg, initial setting time is controlled at 50-80 minutes; The particle size of the medium sand meets the fineness modulus between 2.3 and 3.0, and the mud content is 1% to 3%.
4. The environmentally friendly recycled concrete according to claim 1, characterized in that: The recycled concrete aggregate reshapes its molecular structure to enhance its internal crystallinity and bonding strength. The recycled concrete aggregate has an n+1-level branched structure, which increases the contact area between the aggregate and the cement paste and improves the interface bonding force. Introducing molecules capable of inducing mineralization on the graphene surface, thereby promoting the growth of hydroxyapatite on the graphene surface, to obtain the hydroxyapatite-graphene composite material, wherein hydroxyapatite and graphene are linearly arranged in the composite material, and / or a secondary pre-network structure is constructed, wherein hydroxyapatite serves as a network node and graphene sheets serve as a connecting bridge to form a three-dimensional interconnected network; The rice husk ash is subjected to chemical modification and silanization treatment to improve the hydrophobicity of its surface, and the nano-scale particles of the rice husk ash are utilized to achieve effective filling in the microstructure of concrete; A pre-network structure is designed in the recycled plastic particles so that the recycled plastic particles form a Y-shaped network layout in the concrete, thereby enhancing the crack resistance and toughness of the concrete; The fly ash and slag powder exist in the concrete in the state of molecules or molecular clusters.
5. The environmentally friendly recycled concrete according to claim 1, characterized in that: In the hydroxyapatite-graphene composite material: Synthesize hydroxyapatite nanosheets with a 3:1 aspect ratio to optimize their interfacial interaction with graphene; and / or utilizing an external field to induce hydroxyapatite crystals to grow along the y-axis direction on the graphene surface to form an orderly crystal orientation; And / or construct a multi-level hydroxyapatite structure on the graphene surface, including nanowire arrays and nanosheet stacks, to increase the interface area and enhance the interaction, wherein the interface area is set to IA, then: IA=\sum_{j=1}^{m}A_j Among them, A_j is the surface area of the j-th layer structure, and m is the number of layers; IE=\sum_{k=1}^{l}E_k Where IE is the interaction energy, E_k is the energy of the kth interface interaction, and l is the number of interfaces; and / or utilizing active groups on the graphene surface to chemically react with phosphate or calcium ions on the hydroxyapatite surface to form stable chemical bonds, thereby improving the interfacial bonding strength; And / or introducing polymers or biomolecules with amphiphilic properties between graphene and hydroxyapatite to form a hybrid interface, which can serve as a bridge to connect graphene and hydroxyapatite and optimize the interaction between them to achieve more efficient interface energy transfer and stress dispersion.
6. A process for preparing environmentally friendly recycled concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: First, put silicate cement, slag powder, fly ash and medium sand into a dry mixer for dry mixing. Use the graded feeding method, that is, first add the medium sand with larger particles, then add the fine powder materials fly ash and slag powder, and finally add silicate cement to ensure that the components are evenly distributed. After the initial dry mixing, the aggregate and rice husk ash are pre-screened, and slowly added according to the particle size, and continue to dry mix until uniform; S2: In another mixing container, use deionized water or purified water, slowly add the water reducer into the water, and stir with a stirrer to ensure that the water reducer is completely dissolved to form a uniform wet mixture; S3: slowly add the wet mix to the dry mix, and start the wet mixer for wet mixing. During the wet mixing process, the hydroxyapatite-graphene composite material and the recycled plastic particles are pre-mixed with a small amount of water to form a slurry by a spraying method, and then the slurry is evenly sprayed into the wet mixer through a spray device to ensure that these components are evenly distributed in the concrete; S4: Pour the evenly mixed concrete material into the mold, perform molding operation, and use a vibrating table or vibrator to compact it to ensure that the concrete is densely filled in the mold without voids to obtain recycled concrete.
7. The process for preparing an environmentally friendly recycled concrete according to claim 6, characterized in that: The following preprocessing steps are also included: Pretreatment of recycled concrete aggregate: Select recycled concrete aggregate with a particle size of 5-20mm, ensure that its water absorption rate is 1%-5%, and calculate its apparent density according to the water absorption rate W of the aggregate by the formula ρ=2.7 / (2.7W+1), where W is the water absorption rate and ρ is the apparent density of the recycled concrete aggregate, so as to facilitate subsequent batching, clean the aggregate and remove impurities and dust on the surface; Preparation of hydroxyapatite-graphene composite material: hydroxyapatite is prepared by chemical precipitation method, and graphene is uniformly deposited on its surface to form a composite material, and the area ratio of graphene in the composite material is controlled to be 0.5%-2%, and the particle size is 10-100nm; Preparation and treatment of rice husk ash: Incinerate rice husk at high temperature, control the temperature at 600-800°C to obtain rice husk ash, and ensure that the particle size of the rice husk ash is 10-45μm and the specific surface area is 55-100m2 / g.
8. The process for preparing an environmentally friendly recycled concrete according to claim 6, characterized in that: The following preprocessing steps are also included: Treatment of recycled plastic particles: Select recycled plastic particles with a shape close to spherical, and control the particle size to 1-5mm to reduce its impact on the fluidity of concrete, and clean and dry the particles; Preparation of other components: ensure that the fineness of fly ash meets the requirements of 45μm sieve residue between 2% and 20%, loss on ignition is controlled at 1% to 5%, specific surface area of slag powder is controlled at 350-450m2 / kg, 7-day activity index is 75% to 99%, specific surface area of Portland cement is 300-500m2 / kg, initial setting time is controlled at 50-80 minutes, particle size of medium sand meets the requirements of fineness modulus between 2.3 and 3.0, and mud content is 1% to 3%.
9. The process for preparing an environmentally friendly recycled concrete according to claim 6, characterized in that: Also includes: S5: The formed concrete is cured, the curing temperature is controlled within the range of 20±5℃, the humidity is maintained above 90%, and the curing time is 28-80 days.